2018
DOI: 10.3390/s18061720
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Signal Complexity Analysis in Epileptic Seizure Monitoring: A Topic Review

Abstract: Complexity science has provided new perspectives and opportunities for understanding a variety of complex natural or social phenomena, including brain dysfunctions like epilepsy. By delving into the complexity in electrophysiological signals and neuroimaging, new insights have emerged. These discoveries have revealed that complexity is a fundamental aspect of physiological processes. The inherent nonlinearity and non-stationarity of physiological processes limits the methods based on simpler underlying assumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 121 publications
(133 reference statements)
0
11
0
Order By: Relevance
“…For example, Mohammadi et al recorded brain signals, while subjects performed an attention stimulating task, and Ahmadlou et al used an innovative approach combining wavelets, nonlinear analysis, and neural networks. Furthermore, nonlinear EEG analysis has been successfully applied to diagnose other diseases and disorders including autism (Hadoush et al 2019;Bhat et al 2014;Grossi et al 2019), epilepsy (da Silva 2008Mei et al 2018), bipolar disorder, and schizophrenia (Khaleghi et al 2015;Cutler and Neufeld 2019;Sadatnezhad et al 2011). The efficacy of these nonlinear approaches is not limited to EEG analysis, and the positive results of their applications can also be observed in the analysis of neuroimaging data such as functional magnetic resonance imaging (fMRI) (Kam et al 2017;Sokunbi et al 2014;Sidhu 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Mohammadi et al recorded brain signals, while subjects performed an attention stimulating task, and Ahmadlou et al used an innovative approach combining wavelets, nonlinear analysis, and neural networks. Furthermore, nonlinear EEG analysis has been successfully applied to diagnose other diseases and disorders including autism (Hadoush et al 2019;Bhat et al 2014;Grossi et al 2019), epilepsy (da Silva 2008Mei et al 2018), bipolar disorder, and schizophrenia (Khaleghi et al 2015;Cutler and Neufeld 2019;Sadatnezhad et al 2011). The efficacy of these nonlinear approaches is not limited to EEG analysis, and the positive results of their applications can also be observed in the analysis of neuroimaging data such as functional magnetic resonance imaging (fMRI) (Kam et al 2017;Sokunbi et al 2014;Sidhu 2019).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative representation also used takes the time-frequency transformation of that same signal segment, then assumes the magnitude squares of the frequency samples in the transform domain as representing the energy in the frequency components. On the one hand, the energy in their studies is not time-sensitive for rapid changes in EEG, which are known to be nonlinear and nonstationary [20]. Thus, those energy-based features could not reflect the nonlinear and nonstationary character of energy in seizures effectively.…”
Section: Introductionmentioning
confidence: 96%
“…The complexity of EEG signals and functional status in the brain during epileptic seizures can be quantitatively evaluated by complexity (Mei et al, 2018). Previous studies have demonstrated that the complexity of EEG signals during epileptic seizures is lower than that in healthy humans (Wen-Chin et al, 2015; Noel et al, 2017).…”
Section: Introductionmentioning
confidence: 99%